Regional Assembly Supervisory Effectiveness of Supervision in Efforts to Increase The Professionalism of Notary in The Region of Purwokerto and Purbalingga - Yuliarti Yuliarti; Amin Purnawan (Jurnal Akta, 2018)
Supervisory Council is an entity that has the authority to implement the guidance and supervision of a Notary. Regional Supervisory Council (MPD) is formed in the District / City to develop and supervise the notaries who have work areas Regency / City, in accordance with Article 70 UUJN.The purpose of this study was to analyze the effectiveness of the supervision of the Regional Supervisory Council and the barriers and surveillance solutions Regional Supervisory Council in an effort to increase the professionalism of a notary in Purwokerto and Purbalingga region. This study uses empirical juridical approach, whereas the method of data collection with the literature study and interviews.Results of research supervision by the MPD in Purwokerto and Purbalingga is still not effective, and can not improve the professionalism of a notary in the region of, because they found many violations of the code of conduct. Obstacles encountered MPD is a shortage of funds, lack of secretarial offices and infrastructure that support the implementation by both the duty and authority MPD limited authority and lack of legal awareness of some of the Notary. Some of the possible solutions is to build its own secretary building with the infrastructure that support the implementation of the duties and authority both MPD and monitoring internal, external, repressive and preventive.Keywords: MPD; Supervision Notary Code of Ethics Violations